2005
DOI: 10.1128/jvi.79.24.15398-15404.2005
|View full text |Cite
|
Sign up to set email alerts
|

Unique Ligand Binding Sites on CXCR4 Probed by a Chemical Biology Approach: Implications for the Design of Selective Human Immunodeficiency Virus Type 1 Inhibitors

Abstract: The direct fusion of viral and target cell membranes required for human immunodeficiency virus type 1 (HIV-1) entry is initiated by the primary receptor, CD4, and a chemokine receptor, usually CXCR4 or CCR5. Chemokine receptors are members of the G-protein-coupled receptor (GPCR) superfamily that possess seven transmembrane (TM) domains. Because of its importance in the development of AIDS, CXCR4 has been explored as a new target for drug discovery to combat the AIDS epidemic (3,8,10). As the natural ligands o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
112
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(123 citation statements)
references
References 20 publications
11
112
0
Order By: Relevance
“…Note that we have tested various strains of gp120, including both X4-and R5-preferring gp120, and found that many of them caused neurotoxicity in RCCs. 3 Although the possibility remains that these CXCR4-specific SMM-chemokines could activate other known or unknown signaling pathways, the importance of steric hindrance in their neuroprotective mechanism is further supported by our mutational analysis of their binding sites, which shows overlap in the CXCR4 binding residues of these SMM-chemokines with X4-preferring gp120 but not with SDF-1␣ (48,49). Another mechanism whereby CCR5-selective ligands could suppress the neuroprotective action of these new CXCR4 antagonists would be heterologous desensitization (50,51), but such an effect need not be invoked here because the CCR5 ligands RCP188, RCP189, and gp120 BAL are neurotoxic on their own.…”
Section: Mechanism(s) By Which Antagonist Ccr5-selective Smm-mentioning
confidence: 66%
“…Note that we have tested various strains of gp120, including both X4-and R5-preferring gp120, and found that many of them caused neurotoxicity in RCCs. 3 Although the possibility remains that these CXCR4-specific SMM-chemokines could activate other known or unknown signaling pathways, the importance of steric hindrance in their neuroprotective mechanism is further supported by our mutational analysis of their binding sites, which shows overlap in the CXCR4 binding residues of these SMM-chemokines with X4-preferring gp120 but not with SDF-1␣ (48,49). Another mechanism whereby CCR5-selective ligands could suppress the neuroprotective action of these new CXCR4 antagonists would be heterologous desensitization (50,51), but such an effect need not be invoked here because the CCR5 ligands RCP188, RCP189, and gp120 BAL are neurotoxic on their own.…”
Section: Mechanism(s) By Which Antagonist Ccr5-selective Smm-mentioning
confidence: 66%
“…Three of these critical residues are buried directly below the CXCR4 signal initiator residues discussed above. These residues are F292 7.43 , which has been previously shown to be important for CXCR4 activity (17,19), A291 7.42 , which has a known role in introducing constitutive activity in CCR5 (27), and W252 6.48 , which is part of the well-characterized CWxP rotamer motif (28,29). Homologous positions in the A2AR structure (H278 7.43 and S277 7.42 ) have been shown to move closer to helix III upon agonist binding (30), supporting an important role for these residues in GPCR signal transmission.…”
Section: Significancementioning
confidence: 99%
“…3B, blue). These engagement residues include D97 2.63 at the top of helix II and D187 ECL2 in ECL2, both of which have previously been implicated in binding CXCL12 (9,17,22,23). On the other side of the pocket, D262 6.58 toward the top of helix VI (consistent with previous studies, ref.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that RCP168 and SDF-1a bind overlapping yet distinct sites on the CXCR4 receptor. This pattern of RCP168 binding disrupts HIV infection much more potently than SDF-1a signaling through CXCR4 (nanomolar versus micromolar concentrations), albeit both effects are mediated by modulating the function of this receptor (29). RCP112 is an analogue of viral macrophage inflammatory protein II in which the first 10 amino acids in the NH 2 terminus have been deleted; it has shown a significantly reduced affinity to CXCR4 (30).…”
Section: Inhibition Of Sdf-1a^or Ms-5^induced Chemotaxis By Cxcr4 Inhmentioning
confidence: 99%